The international economy - Ellsworth, P. T.; Leith, J. Clark (New York : Macmillan, 1975)
The book examines developments in the pure theory of international trade and monetary relations and problems balance-of payments difficulties of Europe and United States that changes the character of international monetary systems.
Includes bibliographies and index.
usc 30/01/2019
Loans
Keywords: International trade; International economic relations; Economic policy; Commercial policy